Pengaruh Air dan Sanitasi terhadap Kesehatan Anak Di Indonesia: Analisis Data IFLS - Maizul Rahmizal; Annisa Annisa (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
The role of the sustainable development process has an impact on the fulfillment of access to sanitation and basic services. One of the goals of sustainable development is access to clean water which must start from the household scale. This study aims to analyze the effect of access to water sources and improved sanitation on the health (diarrhea and height for age) of children aged zero and seven years, using the logit and difference-in-difference (DiD) models. This study uses secondary data with various relevant and primary sources that can explain related phenomena. The results show that children in rural areas who access improved sanitation have better height than children who access unimproved sanitation. Meanwhile, the urban sample shows that children who access improved water sources have a lower height than children who access unimproved water sources. This indicates that the quality of clean water sources will determine the level of stunting/availability of children's height in the household.